Наследование по закону в Российской Федерации. Очередность призвания наследников по закону - Novikov, Andrei (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the article is to evaluate the hereditary succession in the Russian Federation. The author presents the order of coming into an inheritance in the Russian civil code.